1996
DOI: 10.1111/j.1365-2222.1996.tb00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased production of IFNγ and increased production of IL‐6 by cord blood mononuclear cells of newborns with a high risk of allergy

Abstract: Our data suggested increased production of IL-6 and decreased production of IFN gamma of cord blood mononuclear cells appear to be the hallmark of newborns from the high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 40 publications
4
60
0
Order By: Relevance
“…Impaired IFN-g at birth may facilitate skewing of T-cell differentiation toward a Th2 phenotype, thereby predisposing to subsequent development of atopic wheezing and asthma in children (33,34). However, deficient IFN-g may also reflect either decreased maturation of CD8 1 T cells or decreased numbers of NK cells or Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired IFN-g at birth may facilitate skewing of T-cell differentiation toward a Th2 phenotype, thereby predisposing to subsequent development of atopic wheezing and asthma in children (33,34). However, deficient IFN-g may also reflect either decreased maturation of CD8 1 T cells or decreased numbers of NK cells or Th1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present authors showed that the capacity of CD4z Th-cells from infants at high risk (HR) of atopy to produce both Th1 and Th2 cytokines was reduced relative to their low risk (LR) counterparts; however, the reduction in IFN-c was greatest, resulting in a relative Th2 "skewing" of responsiveness in the HR children. These findings have since been extended to CBMC in confirmatory studies from a range of independent laboratories [21][22][23][24][25][26].…”
Section: T-cell Immunity To Inhalant Allergens: the Basis Of Variatiomentioning
confidence: 95%
“…Clinical studies have demonstrated that reduced IFN-␥ secretion in neonates is associated with the subsequent development of atopy (53)(54)(55). Furthermore, a predisposition toward the overproduction of Th1 cytokines may protect against atopy, because patients with multiple sclerosis (56), rheumatoid arthritis (57), or tuberculosis (58), conditions associated with increased production of Th1 cytokines, have a reduced predisposition toward the development of atopy.…”
Section: Discussionmentioning
confidence: 99%